Influence of Spontaneous Nystagmus with Eyes Closed on Computerized Vestibular Exam of Patients with Chronic Peripheral - Shin, Elizabeth; Manso, Andréa; Ganança, Cristina Freitas (Arquivos Internacionais de Otorrinolaringologia, 2010)
Introduction: The spontaneous nystagmus with eyes closed (NEOF) can modify the results obtained during some evidence of vestibular, leading to erroneous conclusions.Objective: To characterize the patients and the type of influence on the evidence of NEOF vectonystagmography digital.Method: Retrospective study based on survey charts of patients with the presence of NEOF vectonystagmography digital, in the Outpatient Equilibriometria UNIFESP-EPM, in the years 2000 to 2007. Comparisons were made between genders, ages, direction, angular velocity of NEOF, completion of entrance examination and its influence on the results of caloric testing.Results: We found 73.7% of the population was female, mean age of 55.08 years; NEOF prevalence of horizontal and angular velocity smaller than 7°/s in 86.7%. 59% had some kind of influence caused by the caloric test NEOF as inversion, hyporeflexia, hyperreflexia, nystagmus directional preponderance (NDP) and labyrinthine preponderance (LP) changed. The most prevalent findings were normal vestibular tests (EVN) and bilateral irritative peripheral vestibular syndrome (BIPVS). 38.7% caloric ice and realized these cases it was possible to reach a conclusion in 79%.Conclusion: The NEOF most common was the horizontal type, with VACL less than 7°/s, influencing the majority of examinations and only the results of caloric testing the air, with reversal of post-caloric nystagmus, hyperreflexia and hyporeflexia, NDP and PL altered; the findings were more prevalent and BIPVS EVN, and the caloric test the influence of ice withdrew NEOF in most individuals, enabling to reach a final conclusion.
Keywords: vertigo; electronystagmography; physiological nystagmus